High power laser handbook - Injeyan, Hagop, 1952-; Goodno, Gregory D. (New York : McGraw-Hilll, 2011)
'In-depth details on kilowatt level high-power lasers and their commercial, industrial, and military applicationsHigh Power Laser Handbook introduces the physics and engineering of high-power laser sources as well as their most relevant applications. This work provides a useful and up-to-date reference by compiling, in a single source, a description of the state of the art across a broad range of laser technologies. The book emphasizes phenomenology over first principles derivations to streamline the presentation and enable discussion of applications. High Power Laser Handbook Is edited by three engineers from industry leader Northrop Grumman Presents thorough physical principles of high-power lasers Includes all types of high-power lasers including gas lasers, chemical lasers, free electron lasers, semiconductor lasers, and SSL Covers typical performance parameters for each major class of lasers and what constitutes'high power' for a particular class Features examples of real-world applications The state of the art of high-power lasers: General Principles of Lasers; Gas Lasers; Chemical Lasers; Free Electron Lasers; Semiconductor Lasers; Solid State Lasers; Fiber Lasers; Beam Combining; Nonlinear Processes and Wavelength Conversion'--
'High Power Laser Handbook introduces the physics and engineering of high-power laser sources as well as their most relevant applications. This work provides a useful and up-to-date reference by compiling in a single book a description of the state of the art across a broad range of laser technologies. The book emphasizes phenomenology over first principles derivations to streamline the presentation and enable discussion of applications. Its level is appropriate for professional engineers who have some background in optics and light-particle interactions, but are not necessarily experts in lasers. The book also serves as a supplementary course or reference material for advanced undergraduates or graduate students'--
Includes bibliographical references and index.
Keywords: High power lasers